Natural Sciences, Mathematics, Language and History Teacher Conceptions Regarding Assessments - Arancibia Herrera, Marcelo (2019)
This is a qualitative study that aims to characterize teacher conceptions from four curricular areas: Natural Sciences, Mathematics, Language and History. The study participants all work at various high schools throughout Chile (both public and private institutions in three regions of the country). Specific objectives include defining, analyzing and clustering their conceptions through phenomenographic analysis based on answers obtained from a semi-structured interview. The data obtained was used to compound an analytic matrix that explains differences and similarities among teachers from hailing from different academic areas. We did find that there were more similarities than differences among teacher conceptions. Finally, the paper discusses the relevance of identifying teacher conceptions with regards to assessments since it is an important didactic tool that serves to enhance the curriculum.